Environmentally Modulated Repeat Evolution of Polymorphic Arctic Charr Life History Traits - Grenier, Gabrielle; Smalås, Aslak; Kjær, Runar; Knudsen, Rune (Frontiers in Ecology and Evolution, 2021)
Sympatric Arctic charr, Salvelinus alpinus (L. 1758), morphs have flexible but repeated life history strategies tested across five Norwegian lakes. In several Scandinavian polymorphic Arctic charr populations differentiated by their diet and habitat use, a large littoral omnivorous (LO) morph commonly cooccurs with a smaller profundal spawning (PB/PZ) morph. A third, large piscivorous (PP) morph is also known to occur within a portion of Arctic charr populations in the profundal habitat along with the PB/PZ individuals. Life history traits, such as age at maturity, growth, and diet are known to differ among coexisting morphs. Notably, the PP morph was the longest morph with the oldest age at maturity while the PB/PZ morph showed the shortest lengths overall and youngest age with LO morph being intermediate in both traits. Growth parameters differed across all the morphs. When examining growth within morph groups, the LO morph was found to have different growth across all lakes, while similar reproductive investments and different energy acquisition patterns were seen within the PB/PZ and PP morphs. These results suggest repeat evolution in several life history strategies of reproductively isolated Arctic charr sympatric morphs, notably for the first time in the PP morph, while also highlighting the importance of the local environment in modulating life history traits.